The Effect of Career Development on Turnover Intention: The Mediating Role of Job Satisfaction among Generation Z Employees - Epi Parela; Hujaimatul Fauziah (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study examines the effect of career development on turnover intention with job satisfaction as a mediating variable among Generation Z employees. The study addresses the growing challenge of retaining younger employees who tend to place strong emphasis on career growth, meaningful work, and organizational support. Using a quantitative explanatory design, data were collected through questionnaires from 186 Generation Z employees working in various organizations. The data were analyzed using descriptive statistics, validity and reliability tests, correlation analysis, and hypothesis testing through regression-based mediation analysis. The results show that career development has a significant positive effect on job satisfaction and a significant negative effect on turnover intention. Job satisfaction also has a significant negative effect on turnover intention. In addition, job satisfaction partially mediates the relationship between career development and turnover intention. These findings indicate that career development can reduce employees’ intention to leave both directly and indirectly by improving job satisfaction. The study highlights the importance of career development as a strategic human resource practice for enhancing satisfaction and retaining Generation Z employees in increasingly competitive work environments.